Analisis Kontrastif Kata Sifat Dalam Bahasa Arab Dan Bahasa Inggris - M.Hum, khasanah (Journal of Arabic Language and Literature (ALLAIS), 2023)
This study aims to conduct a contrastive analysis of adjectives in Arabic and English. The study will compare the characteristics, usage, and syntactic structure of adjectives in both languages with the aim of identifying the similarities and differences that exist. The methodology of this research is based on the contrastive approach which allows comparing the linguistic systems of two languages systematically. The research data will be collected from Arabic and English textual sources, such as textbooks, journal articles, and language corpus. Data collection will involve identifying the most common and representative adjectives in both languages, as well as an in-depth analysis of the syntactic attributes and functions attached to those adjectives. The research will address differences and similarities in terms of the grammatical categories of adjectives, such as tense changes, word formation, and the syntactic roles that adjectives assume in sentences. Contrastive analysis will be conducted in semantic, morphological, and syntactic aspects with a focus on the differences between Arabic and English. The results of this study are expected to provide a better understanding of the structural and functional differences of adjectives in Arabic and English. The findings of this study can be useful for second language learners, translators, and curriculum developers in designing effective teaching methods and overcoming common mistakes that often occur when learning Arabic or English.